Effect of amino acid infusion during cesarean delivery on newborn temperature: a randomized controlled trial - Krishna Pokharel; Asish Subedi; Mukesh Tripathi; Binay Kumar Biswas (BMC, 2021)
Abstract Background The effect of maternal amino acid (AA) infusion before and during cesarean delivery on neonatal temperature remains unknown. We hypothesized that thermogenic effects of AA metabolism would help maintain body temperature of newborn babies and their mothers. Methods Seventy-six parturients scheduled for elective singleton term cesarean delivery were equally randomized to receive intravenous 200 ml of AA or placebo approximately 1 h before subarachnoid block (infusion rate:100 ml/h). The primary outcome was the newborn rectal temperature at 0, 5 and 10 min after birth. The secondary outcomes included the maternal rectal temperature at six time-points: T0 = before starting study solution infusion, T1 = 30 min after starting infusion, T2 = one hour after starting infusion, T3 = during spinal block, T4 = half an hour after spinal block, T5 = at the time of birth and T6 = at the end of infusion, as well as maternal thermal discomfort and shivering episodes. Results There were no differences in newborn temperature between the two groups at any of the time-points (intervention-time-interaction effect, P = 0.206). The newborn temperature (mean [95%CI] °C) at birth was 37.5 [37.43-37.66] in the AA and 37.4 [37.34-37.55] in the placebo group. It showed a significant (P < 0.001) downward trend at 5 and 10 min after birth (time effect) in both groups. One neonate in the AA and five in the placebo group were hypothermic (temperature < 36.5 °C) (P = 0.20). There was a significant difference in the maternal temperature at all time points between the two groups (Intervention-time interaction effect, P < 0.001). However, after adjustment for multiplicity, the difference was significant only at T6 (P = 0.001). The mean difference [95%CI] in temperature decline from baseline (T0) till the end of infusion (T6) between the two groups was − 0.39 [− 0.55;− 0.22] °C (P < 0.0001). Six mothers receiving placebo and none receiving AA developed hypothermia (temperature < 36 °C) (P = 0.025). Maternal thermal discomfort and shivering episodes were unaffected by AA therapy. Conclusions Under the conditions of this study, maternal AA infusion before and during spinal anesthesia for cesarean delivery did not influence the neonatal temperature within 10 min after birth. In addition, the maternal temperature was only maintained at two hours of AA infusion. Trial registration ClinicalTrials.government, Identifier NCT02575170 . Registered on 10th April, 2015 - Retrospectively registered.